Overexpression of NNT-AS1 Activates TGF-β Signaling to Decrease Tumor CD4 Lymphocyte Infiltration in Hepatocellular Carcinoma. (24th December 2020) - Wang, Yakun; Yang, Lei; Dong, Xichen; Yang, Xin; Zhang, Xinxue; Liu, Zhe; Zhao, Xin; Wen, Tao
Abstract : Nicotinamide nucleotide transhydrogenase-antisense RNA1 (NNT-AS1) is a long noncoding RNA (lncRNA) that has been shown to be overexpressed in hepatocellular carcinoma (HCC). However, the molecular mechanism involving NNT-AS1 in HCC remains to be extensively investigated. The activation of TGF- β signaling inhibits tumor-infiltrating lymphocytes (TILs) and results in tumor immune evasion. We thus planned to explore the mechanism by which NNT-AS1 activates the TGF- β signaling pathway and inhibits TILs in HCC. High levels of NNT-AS1 were detected in HCC tissues by both RNAscope and real-time quantitative PCR (RT-qPCR) assays. The levels of proteins involved in TGF- β signaling and those of CD4 T lymphocytes were quantified by immunohistochemistry (IHC). HCC cell lines (HepG2 and Huh7) were used to explore the effects of NNT-AS1 on TGF- β signaling activation. In these analyses, RNAscope detection demonstrated that NNT-AS1 levels were significantly increased in HCC cancer tissues (P = 0.0001 ). In addition, the elevated NNT-AS1 levels in cancer tissue were further confirmed by RT-qPCR analysis of HCC cancer tissues (n = 64 ) and normal tissues (n = 26 ) (P = 0.0003 ). Importantly, the overall survival time of HCC patients who exhibited higher levels of NNT-AS1 expression was significantly shorter than that of HCC patients who had lower levels of NNT-AS1 expression (P = 0.0402 ). Further mechanistic investigation indicated that NNT-AS1 inhibition significantly decreased the levels of TGF- β, TGFBR1, and SMAD5 in HCC cells. In HCC tissues, IHC detection showed that relatively high NNT-AS1 levels were associated with a reduction in infiltrated CD4 lymphocyte numbers. In conclusion, this research identifies a novel mechanism by which NNT-AS1 impairs CD4 T cell infiltration via activation of the TGF- β signaling pathway in HCC.